THE EFFECT OF OVAPRIM DOSES ON OVULATION AND EGG QUALITY OF INGIR-INGIR (Mystus nigriceps) - Deasy Arisandy; Sukendi '; Netti Aryani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted in June 2014 in the Fish Hatchery and Breeding Laboratory of the Fisheries and Marine Sciences Faculty University of Riau. The research was to determine the effect of ovaprim on ovulation and egg quality of ingir-ingir (Mystus nigriceps). The method used is an experimental method with a completely randomized design (CRD) with four treatments and three replications. Treatment in this study were P0 (NaCl 0,9% dose of 1 ml / kg body weight) P1 (ovaprim dose of 0,5 ml / kg body weight) P2 (ovaprim dose of 0,7 ml/ kg body weight) and P3 (dose ovaprim 0,9 ml / kg body weight).The results of the research showed that the ovaprim doses 0.7 ml / kg body weight gave the optimum result inter of latent period (6,37 hours), number of egg striping (315 eggs / gram broodstock), increase the diameter eggs (0,038 mm) and percent increase egg maturation (14,3%), and the ovisomatik index (9,85%).Keywords: Ovaprim doses, Ovulation, Ovisomatik indeks and egg quality